Introduction to the Special Issue: Divorce in the Canadian Context—Interventions and Family Processes - Chang, Jeff; Kier, Cheryl A. (Canadian Journal of Counselling and Psychotherapy, 2016)
In this introduction, we describe the prevalence of divorce in Canada, list some of the effects of divorce on children and adults, and emphasize the need for Canadian counsellors to be competent and informed about the processes of divorce and have a repertoire of useful interventions. We conclude the introduction with an overview of the six articles that make up this special issue.